2019
DOI: 10.1177/0300060519879591
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of FRAX in postmenopausal Asian women with and without type 2 diabetes mellitus: a retrospective observational study

Abstract: Objective To compare the fracture risk in postmenopausal Asian women with or without type 2 diabetes mellitus (T2DM). Methods The study cohort comprised data from consecutive postmenopausal women with T2DM that were retrieved from a prospectively maintained institutional database from 2001 to 2009. Postmenopausal women without DM from the Medical Examination Center from 2001 to 2009 formed the control cohort. The primary endpoint was the World Health Organization Fracture Risk Algorithm (FRAX, revised 2013) sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
1
4
0
1
Order By: Relevance
“…As previously stated, the management of fracture risk in the T2DM population remains challenging since BMD tends to be relatively preserved or even higher than in healthy subjects [ 2 , 3 ]. We found out that FRAX-Port® constitutes an easy and effective alternative tool to predict fracture risk within this population and can guide the decision on performing bone densitometry and starting anti-osteoporotic therapy, which is consistent with previous studies [ 5 - 7 ].…”
Section: Discussionsupporting
confidence: 90%
“…As previously stated, the management of fracture risk in the T2DM population remains challenging since BMD tends to be relatively preserved or even higher than in healthy subjects [ 2 , 3 ]. We found out that FRAX-Port® constitutes an easy and effective alternative tool to predict fracture risk within this population and can guide the decision on performing bone densitometry and starting anti-osteoporotic therapy, which is consistent with previous studies [ 5 - 7 ].…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, compared with these patients without DM, a given T-score or FRAX score was associated with higher fracture risk in older adults with DM (47). This finding has confirmed the useful of BMD T-score and FRAX score for clinical evaluation of fracture risk, and prompted a series of subsequent studies (52,53).…”
Section: Authorsmentioning
confidence: 66%
“… 22 Similarly, a study in postmenopausal Asian women found that the non-diabetic group had a lower BMD than the T2DM group. 23 Likewise, in another retrospective clinical study from Rome, T2DM patients were found to have significantly higher mean femoral neck BMD and T-score values than non-diabetic. 24 The reason for the incongruity in the BMD results for T2DM versus non-diabetic subjects in various studies is not clear; however, differences in the age, BMI, menopausal status, and other baseline characteristics between T2DM subjects and the non-diabetics in some studies may partly clarify this inconsistency.…”
Section: Discussionmentioning
confidence: 91%
“…A study carried out by Ohira et al 25 included that 47,389 Japanese women showed FRAX for major osteoporotic fracture risk was not significantly different between individuals with T2DM and non-diabetics, despite the fracture rate in the past 5 years being significantly higher in the diabetic group. In contrast, a study carried out by Wang et al 23 that included 1014 individuals )500 T2DM( found that T2DM had a higher FRAX compared with the non-diabetics group, even after controlling age, gender, BMI, smoking condition, alcohol intake, and low-density lipoprotein levels. Conversely, in another study, the FRAX of both MOF and HF was considerably lower in the entire sample and in males with diabetes than in control subjects, but no significant differences were seen between women with diabetes and control subjects.…”
mentioning
confidence: 83%
See 1 more Smart Citation